Toxicity of Anethole and the Essential Oils of Lemongrass and Sweet Marigold to the Parasitic Mite Varroa destructor and Their Selectivity for Honey Bee (Apis mellifera) Workers and Larvae - Qodratollah Sabahi; Mollah Md. Hamiduzzaman; Juan S. Barajas-Pérez; Jose M. Tapia-Gonzalez; Ernesto Guzman-Novoa (Psyche: A Journal of Entomology)
This study examined the toxicity of anethole and that of the essential oils of lemongrass (Cymbopogon citratus) and sweet marigold (Tagetes lucida) to the mite Varroa destructor and to honey bee workers and larvae. Anethole was the most toxic compound to V. destructor (LC50: 304.9 μg/ml), whereas Tagetes oil was the least toxic (LC50: 1256.27 μg/ml). The most and least toxic compounds to worker bees were anethole and Tagetes oil with LD50s of 35942 and 85381 μg/ml, respectively. For larvae, Tagetes oil was the most toxic compound (LD50: 9580.7 μg/ml) and anethole the least toxic (LD50: 14518.0 μg/ml). Anethole and Cymbopogon oil had the highest selectivity ratios. The expression of AChE, a gene that regulates the production of acetyl cholinesterase, a detoxifying enzyme, was not altered in bees treated with the plant compounds at 48 h post-treatment. This study showed that anethole and Cymbopogon oil have potential for controlling Varroa mites and seem to be relatively safe for larvae and adult honey bees.